Intelligent robotic system for home services : development of mobile robot mapping system using encoder feedback - Qin, Lang (2011)
With the increasingly reliance on robotic technology in human’s life, research in home service robot becomes a popular area in robot development. This project is to design and build a domestic helper which is able to provide assistances to elderly people. The robot developed by author and his group is able to serve tasks such as following a person, recognizing people’s faces, recognizing human’s speech serving drinks to guests and so on. The author’s objective is to design the motion and navigation system of the robot so that the robot is able to move in the dynamic environment such as in the house. In order to achieve acutely movement, a mapping device with high resolution encoder is designed to provide the feedback for the PID control. This device also recodes the data of travelling and an algorithm is developed to calculate the position of the robot based on this data. The author also developed a path-tracking program to increase the accuracy of the robot motion. All the programs are developed using C language and operating in the micro controller. Based on the RS232 communication method, a communication program is developed to transfer data between the micro controller and the note book PC so that the whole system can function properly.